Promoting global competence and social justice in teacher education : successes and challenges within local and international contexts - Schwarzer, David; Bridglall, Beatrice L., 1968- (Lexington Books, 2015)
Promoting Global Competence and Social Justice in Teacher Education reconceptualizes the purpose of education to include the attainment of global or cosmopolitan perspectives. This goal has important implications for how we not only educate today's students, but also how we prepare teachers to teach in a diverse and complex world in which habits of perspective, inquiry, imagination, empathy, communication, commitment, humility, integrity, and judgment increasingly resonate in importance. This book advocates for preparing teacher candidates to acquire a nuanced, global perspective of their subject areas and be prepared to handle the demands of educating students for our changing global context. To this end, Promoting Global Competence and Social Justice in Teacher Education encourages the development of pedagogical strategies that will enable students to consider multiple perspectives and cultivate respect for diverse peoples and cultures.